2016
DOI: 10.2147/ndt.s99032
|View full text |Cite
|
Sign up to set email alerts
|

Yokukansan improves behavioral and psychological symptoms of dementia by suppressing dopaminergic function

Abstract: Although three drugs, risperidone, yokukansan, and fluvoxamine, have shown equal efficacy in treating behavioral and psychological symptoms of dementia (BPSD) in our previous study, their mechanisms of action are different from one another. Monoamines have attracted attention for their key roles in mediating several behavioral symptoms or psychological symptoms through synaptic signaling. We aimed to clarify the monoamines changed by treatment with each drug in patients with BPSD. The main purpose of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
4
1
Order By: Relevance
“…In contrast to the hypothesis introduced by the previous finding of yokukansan [ 11 ], yokukansankachimpihange did not improve “active symptoms”, as shown by the non-significant effects revealed here on subscales A (Paranoid and Delusional Ideation), B (Hallucinations), C (Activity Disturbances), and D (Aggressiveness).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the hypothesis introduced by the previous finding of yokukansan [ 11 ], yokukansankachimpihange did not improve “active symptoms”, as shown by the non-significant effects revealed here on subscales A (Paranoid and Delusional Ideation), B (Hallucinations), C (Activity Disturbances), and D (Aggressiveness).…”
Section: Discussioncontrasting
confidence: 99%
“…Yokukansan is one of the traditional herbal medicines (Kampo medicine in Japan) that is commonly used for the treatment of BPSD [ 10 ], and some neuropharmacological actions have been reported [ 11 ]. A recent systematic review [ 12 ] described five RCTs with 381 patients, versus controls, that reported that yokukansan significantly decreased BPSD total scores, as well as the BPSD subscale of “active symptoms”, i.e., delusions, hallucinations, and agitation/aggression.…”
Section: Introductionmentioning
confidence: 99%
“…Since modified forms are widely used in combination, the questionnaire in this study included a modified form in response to Ondam-tang. Eokgan-san has been prescribed for restlessness and agitation in children and has been reported to improve the behavioral and psychological symptoms of dementia [ 45 , 46 ] and Tourette’s syndrome symptoms in children and adolescents for a short period of time [ 47 ]. Sihogayonggolmororyeo-tang (written as Chaihu Jia Longgu Muli decoction in Chinese) has been reported to have an antiepileptic effect in an experimental study on rats [ 48 ], and in an SR, it was found to be more effective than conventional medicine in the treatment of post-stroke depression [ 49 ] and insomnia [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are safety issues associated with HM, such as lack of safety monitoring and potential interactions with conventional pharmaceuticals ( Ekor, 2014 ). Fortunately, for some standardized HMs, such as Yokukansan, underlying therapeutic mechanisms for dementia ( Takeyoshi et al, 2016 ), potential interactions with conventional medications ( Soraoka et al, 2016 ) and safety issues have been documented ( Shimada et al, 2017 ). Similarly, a database of some potential herb-drug interactions relevant to the management of cognitive impairment has been recently developed.…”
Section: Discussionmentioning
confidence: 99%